Kajian Kalibrasi Hidrograf Representatif Di Das Samiran Kabupaten Pamekasan - Priombodo, Agus; Limantara, Lily Montarcih; Suhartanto, Ery (Fakultas Teknik, Universitas Brawijaya, 2012)
Samiran watershed is including Semajid River and its tributaries has an approximate to 69,76 km2of number area. This watershed is located in Pamekasan distric, East Java. Samiran catchment area is affected by approximate to 5 rain stations scattered in the watershed. Has not been studied theoretically about the optimum density and dispersal patterns of their rainfall station networks have been installed and comparative studied in hidrograf in the Samiran watershed. Based on the results of the assessment and analysis by using Kagan-Rodda method, it was acquired 3 selected stations, while the Kriging method obtained results 5 selected stations that spreads in the Samiran watershed. Relative error for the design rainfall of Kagan-Rodda method was 14,53 and 13,96 for Kriging method.Ordinat control to get runoff area of 1 mm from watershed is19,378 m3/sec/year by using the method of Collins. It was obtained the average time to peak was 2 hours for GAMA I, peak discharge is 300 m3/sec with a time of peak discharge 14 hour basis. the Limantara hydrograf the average time to peak was 2 hours, peak discharge is 170 m3/sec with a time of peak discharge 8 hour basis. the hydrograf of observatian have the average time to peak at 8 hours, peak discharge is 4,27 m3/sec with a time of peak discharge 11 hour basis.Keywords: Rainfall station networks, Kagan-Rodda, Kriging, Hidrograf